Association between proprotein convertase subtilisin/kexin type 9 and late saphenous vein graft disease after coronary artery bypass grafting: a cross-sectional study. Issue 7 (10th July 2018) - Gao, Jing; Wang, Hai-Bo; Xiao, Jian-yong; Ren, Min; Reilly, Kathleen Heather; Li, Yu-Ming; Liu, Yin
Abstract : Objective: The study aims to explore the association between serum proprotein convertase subtilisin/kexin type 9 (PCSK9) level and saphenous vein grafts disease (SVGD) after coronary artery bypass grafting (CABG). Design: A cross-sectional study. Setting: A secondary hospital in Tianjin City, China. Participants: A total of 231 participants were included in the study. Inclusion criteria were as follows: age ≥18 years, previous CABG surgery at least 12 months ago, at least one SVG for bypass during CABG, abnormal non-invasive test results or recurrent stable angina pectoris by coronary angiography indications, and willing to participate and sign informed consent. Participants with any of the following were excluded from the study: congenital valvular disease, decompensated heart failure, anaemia defined as a haemoglobin level of <12 g/dL in women or <13 g/dL in men, malignant neoplasms, renal failure, severe hepatic disease, thyroid disease, acute or chronic inflammatory disease and chronic obstructive lung disease. Primary outcome measure: SVGD was defined as at least one SVG with significant stenosis (≥50%). Circulating PCSK9 levels were measured using commercial ELISA kits according to the manufacturer's instructions. Results: The mean PCSK9 level in the SVGD group was significantly higher than that in the patent group (275.2±38.6 vs 249.3±37.7, p<0.01). The multivariate logistic regression model revealed a significant association between serum PCSK9 and SVGD (OR 2.08, 95% CI 1.46–2.95) per 1 SD increase in serum PCSK9. Conclusions: The present study is the first to identify an independent association between PCSK9 and late SVGD after adjustment for established cardiovascular risk factors. A multicentre prospective cohort study with large sample size should be conducted in the future to further research this relationship.